Determination of optimal electrospinning distance and applied voltage for polyacrylonitrile electrospun fibre production - Abdul Hamid, Nurfaizey; Akop, Mohd Zaid; Masripan, Nor Azmmi; Wasbari, Faizil; Abdul Munajat, Nurain; Mohamad Wazir, Azmil Arif; Jaafar, Juhana; Othman, ‎Mohd Hafiz Dzarfan; Tucker, Nick (Universiti Malaysia Perlis, 2021)
Electrospinning process is highly dictated by electric field strength. Thus, two key parameters i.e., electrospinning distance and applied voltage, determine the quality of electrospun fibres. Incorrect selection of these parameters will result in poor fibre qualities. There ought to be an optimal combination of electrospinning distance and applied voltage to produce best quality fibres from a given material. In this study, the optimal combination of electrospinning distance and applied voltage was assessed based on consistency of electrospinning process, amount of fibre, fibre morphology, and average fibre diameter. Polyacrylonitrile (PAN) electrospun fibre samples were prepared at different combinations of electrospinning distance and applied voltage. Scanning electron microscopy and image analysis were conducted to assess the quality and average diameter of the fibres. The results indicate that for electrospinning of PAN, the distance should be between 10 and 20 cm with a 15 to 20 kV of applied voltages. Findings from this study is crucial for producing optimal fibre quality in PAN electrospun nanofibre synthesis.